Interface-engineered NiO-TiN nanocomposites synthesized by sol-gel-assisted controlled precipitation: Microstrain-interface coupling and broadband dielectric/AC transport response - Gurgenc, Ezgi; Macit, Cevher Kursat; Guner, Melek; Ayik, Merve; Gurgenc, Turan; Aksakal, Bunyamin (Academic Press Inc Elsevier Science, 2026)
NiO-based dielectric ceramics and nanostructured oxides often exhibit strongly frequency-dependent electrical behavior due to defect-and interface-mediated polarization rather than purely intrinsic lattice response. In this work, pristine NiO and a compositionally systematic series of TiN-containing NiO-TiN nanopowders (1-10 mol. %) were synthesized via a sol-gel-assisted controlled precipitation route while keeping key processing parameters constant to enable reliable structure-property correlations. Phase formation, crystallinity, crystallite-size refinement, and microstrain evolution were examined by XRD using Scherrer and Williamson-Hall analyses, and the microstructural morphology and Ti/N distribution were assessed by FE-SEM/EDX. FT-IR, Raman, and XPS were employed to probe bonding heterogeneity, defect-activated vibrational features, and the surface/nearsurface chemical states relevant to oxide-nitride heterointerfaces. Broadband dielectric spectroscopy was used to evaluate epsilon ', tan delta, and sigma ac over a wide frequency range. TiN incorporation produced a pronounced and non-linear enhancement of epsilon ' despite the lower intrinsic permittivity of pristine TiN. At 1 kHz, epsilon ' increased from 7.155 +/- 0.005 for pristine NiO to 14.854 +/- 0.013 for NiO-TN10, while tan delta remained within a narrow and practically manageable interval of 0.070-0.087, indicating that permittivity gain was not accompanied by disproportionate loss. In parallel, sigma ac exhibited dispersive behavior and increased systematically with TiN content, confirming a tunable transport response in the composites. Overall, the results demonstrate that introducing TiN as a conductive secondary phase is an effective interface-engineering strategy to co-tune permittivity, dissipation, and AC transport in NiO, supporting the practical relevance of NiO-TiN nanocomposites for dielectric components and energy-related functional materials, including capacitive energy storage elements and electromagnetic or microelectronic layers requiring enhanced epsilon ' with controlled loss.
Keywords: Nanocomposite; NiO; Dielectric; Interfacial polarization; AC conductivity; Energy storage materials; Maxwell-Wagner-Sillars polarization